Prevalence of completion of maternity continuum of care and its associated factors in Ethiopia: a systematic review and meta-analysis - Ayenew Mose; Kassahun Haile; Abebe Timerga (BMJ Open, 2022)
Objective The present study aimed to estimate the pooled prevalence of completion of the maternity continuum of care (CoC) and its associated factors in Ethiopia.Study design Systematic review and meta-analysis.Study setting Ethiopia.Study participants A total of 6245 reproductive-age women were included.Primary outcome The pooled prevalence of completion of the maternity CoC.Secondary outcome Factors associated with completion of the maternity CoC.Methods We systematically searched international databases such as PubMed, Scopus, African Journals Online, Google Scholar and Web of Sciences to retrieve related articles. The Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines were used for this study. Publication bias was assessed using the funnel plot and Egger’s test. Evidence of heterogeneity was checked using Cochrane Q test and I2 statistics. Subgroup analysis was computed based on the study regions. Data were analysed using STATA V.14 statistical software. Weighted inverse variance random effect models were used to estimate the pooled prevalence of completion of the maternity CoC.Results The pooled prevalence of completion of maternity continuum care in Ethiopia was 25.82% (95% CI: 16.69% to 34.94%). Urban residence(adjusted odds ratio (AOR)=2.77, 95% CI: 1.99 to 3.86), having secondary and above educational status (AOR=3.50, 95% CI: 2.50 to 50), prepregnancy contraceptive utilisation (AOR=3.25, 95% CI: 2.02 to 5.22), women’s autonomy (AOR=3.81, 95% CI: 2.74 to 5.31), following mass media (AOR=2.51, 95% CI: 1.79 to 3.50), early initiation of antenatal care (ANC) (AOR=4.98, 95% CI: 3.28 to 7.57), planned pregnancy (AOR=2.93, 95% CI: 1.99 to 4.32), birth preparedness and complication readiness (AOR=1.80, 95% CI: 1.29 to 2.51) and distance from a health facility<30 min (AOR=3.29, 95% CI: 2.45 to 4.42) were factors associated with completion of maternity continuum care in Ethiopia.Conclusion The pooled prevalence of completion of maternity continuum care in Ethiopia was low. Therefore, policymakers and stakeholders should improve the completion of ANC, the rate of skilled birth attendants and postnatal follow-up. Enhancing the accessibility of health facilities, women’s awareness and empowering women’s decision-making are recommended.PROSPERO registration number CRD42022312692.